2017
DOI: 10.1080/16546628.2017.1287333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic food consumption on human health; the jury is still out!

Abstract: The most recent systematic literature reviews and meta-analyses have indicated significant and nutritionally-relevant composition differences between organic and conventional foods. This included higher antioxidant, but lower cadmium and pesticide levels in organic crops, and higher omega-3 fatty acids concentrations in organic meat and dairy products. Also, results from a small number of human cohort studies indicate that there are positive associations between organic food consumption and reduced risk/incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 23 publications
(50 reference statements)
0
41
0
1
Order By: Relevance
“…These include higher antioxidant concentrations (particularly polyphenols) in organic crops [10]; increased levels of omega-3 fatty acids in organic dairy products [11][12][13]; and improved fatty acid profiles in organic meat products [14,15]. These compositional differences are comprehensively discussed in several recent reviews [16][17][18][19]. There is preliminary evidence to suggest that these compositional differences may have an effect on plasma levels of certain nutrients including magnesium, fat-soluble micronutrients (α-carotene, β-carotene, lutein, and zeaxanthin), and fatty acids (linoleic, palmitoleic, γ-linolenic, and docosapentaenoic acids) [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include higher antioxidant concentrations (particularly polyphenols) in organic crops [10]; increased levels of omega-3 fatty acids in organic dairy products [11][12][13]; and improved fatty acid profiles in organic meat products [14,15]. These compositional differences are comprehensively discussed in several recent reviews [16][17][18][19]. There is preliminary evidence to suggest that these compositional differences may have an effect on plasma levels of certain nutrients including magnesium, fat-soluble micronutrients (α-carotene, β-carotene, lutein, and zeaxanthin), and fatty acids (linoleic, palmitoleic, γ-linolenic, and docosapentaenoic acids) [20].…”
Section: Introductionmentioning
confidence: 99%
“…The last systematic review into the effect of organic food consumption on health was conducted by Dangour et al in 2010 [35], which was limited to strict inclusion criteria of organic interventions, and Smith-Spangler et al in 2012 [19], which contained only minimal focus on the human health effects of organic food, and a broader focus on nutritional content of organically and conventionally grown food and food safety. Although there have been other more recent reviews on the effects of organic diet on broader aspects of health [16][17][18]21], none have been systematic. The literature has expanded since these earlier systematic reviews, with many cohort and cross-sectional studies being published which compare organic versus conventional dietary intake on a range of health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not simple to conduct epidemiological or intervention studies, because individuals that consume organic foods and dairy products usually have different lifestyles that should be taken into consideration in the definition of these kinds of researches. As recently reported by some authors [48], there are no long-term cohort studies or controlled dietary intervention studies comparing the effects of diets based on organic or conventional food. In this context, the higher cost of organic milk can be justified only by the high cost of the management of these farms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the quality of organic agricultural products is not different from that of conventional agricultural products and will not have different effects on human health [4,5]. Therefore, some consumers have no preference difference between organic agricultural products and conventional products.…”
Section: Introductionmentioning
confidence: 99%